Buggy breakout - Keene, Carolyn; Pamintuan, Macky (New York : Aladdin, 2010)
When someone steals Sonia's pet beetle, it is up to eight- year-old Nancy and the members of her detective club to find it.
Keywords: Insects -- Juvenile fiction; Beetles -- Juvenile fiction; Detective and mystery stories -- Juvenile fiction